2021
DOI: 10.12944/cwe.16.3.13
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Agricultural Soils of National Capital Region, Delhi: Levels and Ecological Risk

Abstract: This study was conducted to assess heavy metals concentrations in agricultural soils in the National Capital Region, Delhi. A total of 84 soil samples were collected from selected agricultural areas located near industries, national highways, state highways, Yamuna floodplain, residential complexes, and wastewater irrigated soils. Heavy metal concentrations, pH, and organic carbon (%) were analyzed in the collected soil samples. The average value of pH, and organic carbon (%) in the soil samples were 7.79±0.49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The major contribution of Cu is agricultural practices, 53 and derived from anthropogenic activities, 54 The Cd concentration is very high in soils due to irrigation drains along with sewage. 38 similar studies stated that high concentration of Cr affected the soil microorganisms. 79&80 Arsenic levels in the present study area observed as S4-15.21 ppm> S3-14.78 ppm> S8-13.27ppm are higher levels and the S6< S1< S7< S2 and S5 are have the minimum levels of the Arsenic, and the mean, standard deviation levels are 3.10689 ± 11.0325.…”
Section: Soil Contamination Assessmentmentioning
confidence: 68%
“…The major contribution of Cu is agricultural practices, 53 and derived from anthropogenic activities, 54 The Cd concentration is very high in soils due to irrigation drains along with sewage. 38 similar studies stated that high concentration of Cr affected the soil microorganisms. 79&80 Arsenic levels in the present study area observed as S4-15.21 ppm> S3-14.78 ppm> S8-13.27ppm are higher levels and the S6< S1< S7< S2 and S5 are have the minimum levels of the Arsenic, and the mean, standard deviation levels are 3.10689 ± 11.0325.…”
Section: Soil Contamination Assessmentmentioning
confidence: 68%
“…The SOC content varies from 0.40% to 0.70% during the winter and summer seasons of both the years (2017–2018 and 2018–2019). Rani et al (2021) observed slightly alkaline soil pH (7.79 ± 0.49), and the organic carbon content 0.53 ± 0.21% in Delhi National Capital Region soil. The pH value of agricultural soils may have been raised due to excessive use of organic fertilizers and continuous crop cultivation.…”
Section: Resultsmentioning
confidence: 98%
“…The values of heavy metals analyzed were detected below the permissible limits of Indian standards given by Awasthi (2000). According to Rani et al (2021), the average concentrations of heavy metals in the agricultural soils of Delhi were determined to be in the following order: Fe > Al > Mn > Zn > Ni > Cr > Cu > Pb > Co > Cd. The alkaline pH in the current study is intended to limit the solubility of heavy metals in agricultural soil since heavy metals often exhibit high solubility at low pH (Shamim et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Organic carbon (OC) is also a significant parameter of agricultural soil because it maintains the bio-availability of HM in soil 29 . A low concentration of OC in soil reduces the soil microbial diversity and biomass through decreasing mineralization.…”
Section: Resultsmentioning
confidence: 99%
“…This study observed that the surface soils ranged from strongly acidic to slightly acidic and sub-surface soils varied from strongly acidic to neutral. Although, Rani et al 29 found the alkaline nature of agricultural soil in Delhi, India and they mentioned that low pH has high solubility of HM in soil. Lower concentrations of pH in soil may decrease HM adsorption and increase soil mobility 70 .…”
Section: Discussionmentioning
confidence: 99%